Rang Gelandang Tuo sebagai Ide Penciptaan Karya Lukis Kontemporer - Muhammad Arief; Yasrul Sami (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This final work aims to visualize the various negative impacts that arise from small communities, from how they earn a living to ending up as midfielders and the impact of small communities' behavior in contemporary works of painting. The hope of this work is to increase public knowledge and awareness and enrich ideas in realizing contemporary painting art. The method the author uses is the art concert method which consists of: (1) Preparation, in the form of observation, gathering information and ideas. (2) Elaboration, to determine the main idea through analysis, abstraction, generalization and transmutation. (3) Synthesis, to realize the concept of the work of art. (4) Realization of concepts into various art media. (5) Finishing it into the final form of the work of art. These stages become a reference for writers in working on works of painting. Based on the understanding and determination of ideas, the author can visualize 10 works with the titles: first